Editorial: Special Issue on Interdisciplinary and Experiential Entrepreneurship Education. (January 2021) - Winkler, Christoph; Winkel, Doan; Shields, Julienne; Barber, Dennis; Levin, Donna; J. Zane, Lee
A group of six colleges and universities (East Carolina University, Iona College, John Carroll University, Millikin University, Rowan University, Worcester Polytechnic Institute) partnered up to co-host the January 2020 USASBE Conference in New Orleans, LA, with the theme Interdisciplinary & Experiential Entrepreneurship Education. The conference thematically aligned its overall program with this special issue, which features scholars and programs representing the arts, design, engineering, liberal arts, physical sciences, STEM, and – yes – business. This editorial further discusses the importance of interdisciplinary entrepreneurship education as an inherent feature of itself to truly evolve as a discipline.